The Principal's Efforts to Overcome the Problem of Teaching and Learning in the Field of Science - Roberto Patabang Allolangi; Asma Kurniati (Postgraduate, University of Mataram, 2023)
The focus of this research problem is to determine how the principal's efforts to overcome the problem of teaching and learning activities at SMAN 9 Tana Toraja. The purpose of the study was to find out the causes: the teacher often gave notes to students while the teacher concerned hung out outside the classroom, and the principal's efforts to overcome so that this incident did not run continuously; there is a lack of cohesiveness between fellow teachers and the principal's efforts to overcome so that teachers can work together, establish family relationships so that the school goals can be achieved; teachers copy the learning tools and the principal's efforts to overcome the teacher's copying of learning tools; students hang around a lot during class hours and the principal's efforts to overcome this situation. Research method: observation, interview, documentary. Findings: 1). Teachers often give notes to students because the classroom atmosphere is bland, students act less respectfully of teachers, the principal does not supervise teachers, teaching materials are lacking, and teachers who teach are not by their educational background. 2). Lack of communication between teachers, rare family gatherings, jealousy between fellow teachers. 3). Almost all teachers copy other teachers' learning tools. 4). Lack of supervision, picket teachers, are less active in controlling the situation at school. Conclusion: homerooms need to organize classrooms neatly, maintain cleanliness, and discipline students, principals must control regularly, make joint rules about discipline in class when teachers carry out teaching and learning processes HP is disabled, fulfillment of facilities and infrastructure, holding training, 2. Holding family meetings; 3. teachers make their learning tools through MGMP; 4. Picket work by the task.